WILL HAUNT YOU - Kirk, Brian, 1977- (London : FLAME TREE PRESS, 2019)
Jesse Wheeler disappeared a couple of years ago, just after playing a reunion gig with his band, The Rising Dead. Rumor has it he had just finished reading a book like the one you're holding now. He's not the only one, either. Supposedly there's a whole bunch of people who've disappeared. But that's probably just a folktale, wouldn't you say?
Keywords: Disappeared persons -- Fiction; Books -- Fiction; Death -- Fiction; Horror fiction; Psychological fiction